2022
DOI: 10.3389/fmed.2022.1066412
|View full text |Cite
|
Sign up to set email alerts
|

Multicentered analysis of percutaneous sclerotherapies in venous malformations of the face

Abstract: ObjectivesTo evaluate the safety and outcome of image-guided sclerotherapy for treating venous malformations (VMs) of the face.Materials and methodsA multicenter cohort of 68 patients with VMs primarily affecting the face was retrospectively investigated. In total, 142 image-guided sclerotherapies were performed using gelified ethanol and/or polidocanol. Clinical and imaging findings were assessed to evaluate clinical response, lesion size reduction, and complication rates. Sub-analyses of complication rates d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For venous malformations, besides conservative management, invasive therapy is indicated in symptomatic VMs to reduce symptoms such as pain, hemorrhage, and impairment of neighboring structures. For VMs percutaneous sclerotherapy is the first-choice invasive treatment method and can be combined with laser therapy or surgical procedures (20,21). However, evidence is low and the choice for the invasive method remains a shared decision between the patient and a multidisciplinary team of specialists (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For venous malformations, besides conservative management, invasive therapy is indicated in symptomatic VMs to reduce symptoms such as pain, hemorrhage, and impairment of neighboring structures. For VMs percutaneous sclerotherapy is the first-choice invasive treatment method and can be combined with laser therapy or surgical procedures (20,21). However, evidence is low and the choice for the invasive method remains a shared decision between the patient and a multidisciplinary team of specialists (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, eight patients were included; five (62.5%) were male, and three (37.5%) were female. Median age was 22 years [total range, 11-56; interquartile range (IQR), [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. One patient had an arteriovenous malformation (classified as Schobinger II and Cho IIIb), four had venous malformations (2x Puig type I, 1x type II and 1x type III), and one each had a mixed venouslymphatic malformation, a glomuvenous malformation and a FAVA (fibroadipose vascular anomaly).…”
Section: Patientsmentioning
confidence: 99%
“…Studies on treatment outcomes of sclerotherapy/embolization often focus on a specific CVM subtype, a specific anatomical location, or a specific agent, and the definition of a successful treatment outcome varies, all of which limits comparability. In recent studies on pediatric patients, a complete response was reported in 11-89% of the patients and improvement in 57-100% [34,48,49,51,54,69,70]. In LMs, bleomycin seems to be the most effective agent, and macrocystic lesions often showed a better response than microcystic and/or mixed lesions [49,53,70].…”
Section: Sclerotherapy/embolizationmentioning
confidence: 98%
“…The technique consists of injecting chemical agents into the CVM with the aim of thrombosing and obliterating the vessels and thereby inactivating the malformation. Initially reserved for patients deemed inoperable, sclerotherapy and embolization have emerged as the treatment of choice in many cases, offering advantages over surgical resection [47][48][49][50]. Various chemicals can be used, such as ethanol, coils, glues, Onyx (ethylene-vinyl alcohol copolymer), bleomycin, polidocanol (aethoxysclerol), doxycycline, and many more [49,[51][52][53][54][55][56][57][58].…”
Section: Sclerotherapy/embolizationmentioning
confidence: 99%
See 1 more Smart Citation